Lessons learned from adapting a remote area health placement from physical to virtual: a COVID-19-driven innovation - Mak, Donna; Russell, K.; Griffiths, D.; Vujcich, Daniel; Strasser, R. (IJME, 2021)
Objectives: To investigate the acceptability and the effectiveness of a virtual adaptation of a well-established, mandatory, community-based pre-clinical remote area health placement in which medical students learn about the social and environmental determinants of health in remote Australia; and make recommendations to guide the delivery of future learning experiences.